Effect of Sugar Concentration on Microbiological and Physicochemical Stability of Soursop Jam - Regina Ilse Marcelina BanoEt; Amanda Priscilla Nainiti; Margarethy Rohanie Mbado; Jemmy J. S. Dethan (Postgraduate, University of Mataram, 2026)
Soursop jam is a local fruit-based product with potential for food diversification; however, its high moisture content increases susceptibility to microbiological deterioration during room-temperature storage. This study aimed to evaluate the effect of different sugar concentrations on the microbiological, physicochemical, and sensory characteristics of soursop jam and to determine its shelf life using a critical limit and risk-based microbiological assessment approach. The novelty of this study lies in the integration of microbiological indicators with physicochemical parameters to explain biological failure during storage of local fruit-based jam products. The experiment used three sugar concentrations, namely 50%, 60%, and 70% (w/w), with duplicate analyses for each treatment. Storage observations were conducted for 20 days at room temperature (27–30 °C), while microbiological analysis referred to ISO 4833-1:2013 and SNI 3746:2008 as the critical microbiological limit. The results showed that initial Total Plate Count values ranged from 23.50 × 10³ to 34.00 × 10³ CFU g⁻¹, which remained below the permissible limit. Moisture content decreased from 48.36% to 36.80% with increasing sugar concentration, while vitamin C content increased from 7.86 to 10.48 mg/100 g. The jam with 60% sugar concentration showed the highest sensory acceptance scores for color (4.64 ± 0.42) and aroma (4.78 ± 0.40). However, visible mold and yeast growth appeared after 20 days of storage in all treatments. Based on the critical limit approach, the shelf life of soursop jam is recommended not to exceed one week under room-temperature storage conditions.